Continuous postoperative pericardial flushing reduces postoperative bleeding after coronary artery bypass grafting: A randomized trial. (January 2021) - Diephuis, Eva C; de Borgie, Corianne A; Zwinderman, A.; Winkelman, Jacobus A; van Boven, Wim-Jan P; Henriques, José P.S.; Eberl, Susanne; Juffermans, Nicole P; Schultz, Marcus J; Klautz, Robert J.M.; Koolbergen, David R
Abstract: Background: Prolonged or excessive bleeding after cardiac surgery can lead to a broad spectrum of secondary complications. One of the underlying causes is incomplete wound drainage, with subsequent accumulation of blood and clots in the pericardium. We developed the continuous postoperative pericardial flushing (CPPF) therapy to improve wound drainage and reduce postoperative blood loss and bleeding-related complications after cardiac surgery. This study compared CPPF to standard care in patients after coronary artery bypass grafting (CABG). Methods: This is a single center, open label, randomized trial that enrolled patients at the Amsterdam UMC, location AMC, Amsterdam, the Netherlands. The study was registered at the 'Netherlands Trial Register', study identifier NTR5200 [1] . Adults undergoing CABG were randomly assigned to receive CPPF therapy or standard care, participants and investigators were not masked to group assignment. The primary end point was postoperative blood loss in the first 12-hours after surgery. Findings: Between the January 15, 2014 and the March 13, 2017, 169 patients were enrolled and assigned to CPPF therapy (study group; n = 83) or standard care (control group; n = 86). CPPF reduced postoperative blood loss when compared to standard care (median differences -385 ml, reduction 76% p =≤0.001), with the remark that these results are overestimated due to a measurement error in part of the study group. None of patients in the study group required reoperation for non-surgical bleeding versus 3 (4%, 95% CI -0.4% to 7.0%) in the control group. None of the patients in the study group suffered from cardiac tamponade, versus 3 (4%, 95% CI -0, 4% to 7.0%) in the control group. The incremental cost-effectiveness ratio was €116.513 (95% bootstrap CI €-882.068 to €+897.278). Interpretation: The use of CPPF therapy after CABG seems to reduce bleeding and bleeding related complications. With comparable costs and no improvement in Qualty of Life (QoL), cost consideration for the implementation of CPPF is not relevant. None of the patients in the study group required re-interventions for non-surgical bleeding or acute cardiac tamponade, which underlines the proof of concept of this novel therapy. Funding: This study was funded by ZonMw, the Netherlands organization for health research and development (project 837001405).